2014
DOI: 10.1111/jam.12467
|View full text |Cite
|
Sign up to set email alerts
|

Molecular differentiation of Pantoea stewartii subsp. indologenes from subspecies stewartii and identification of new isolates from maize seeds

Abstract: Aims: Assays to detect Pantoea stewartii from maize seeds should include differentiation of P. stewartii subsp. stewartii and P. stewartii subsp. indologenes. Methods and Results: Previously published PCR primers for the identification of P. stewartii subsp. stewartii amplified signals from both subspecies using both conventional and quantitative PCR. In MALDI-TOF mass spectroscopy analysis with the Biotyper software (Bruker), subspecies stewartii and indologenes produced identical score values. Analysis again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 21 publications
1
31
0
1
Order By: Relevance
“…indologenes-specific 3614gal primers of Gehring et al (2014) both routine maize seed samples mentioned above were confirmed to be infested with P. stewartii subsp. indologenes-specific 3614gal primers of Gehring et al (2014) both routine maize seed samples mentioned above were confirmed to be infested with P. stewartii subsp.…”
Section: Additional Pcr Tests For P Stewartii Subsp Indologenesmentioning
confidence: 82%
See 4 more Smart Citations
“…indologenes-specific 3614gal primers of Gehring et al (2014) both routine maize seed samples mentioned above were confirmed to be infested with P. stewartii subsp. indologenes-specific 3614gal primers of Gehring et al (2014) both routine maize seed samples mentioned above were confirmed to be infested with P. stewartii subsp.…”
Section: Additional Pcr Tests For P Stewartii Subsp Indologenesmentioning
confidence: 82%
“…indologenes which can be found on maize is of particular importance, as the latter subspecies is neither virulent on maize nor a regulated quarantine organism in any country (Gehring et al, 2014). stewartii in maize samples within the framework of the implementation of quarantine regulations it is essential for diagnostic laboratories to have a specific and sensitive first screening test available that reliably selects for potential positives, which will then have to undergo further tests according to an official testing scheme.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations